Strategi Manajemen Kelas Pada Proses Belajar Mengajar Bahasa Inggris di SD Muhammadiyah Boarding School PrambananSleman - Arif Rifanan (Universitas Islam Negeri Raden Mas Said Surakarta, 2018)
English lessons are not the main subject at elementary school level. But in some schools these subjects become part of the local content or become a superior program offered to parents of students. Delivering English lessons is certainly not easy. There are various students who come to school. Student diversity also goes hand in hand with increasing problems in learning. Therefore there needs to be a good class management. In this study the authors, conducted research on the management strategies of English teacher classes in the teaching and learning process at SD Muhammadiyah Boarding School Prambanan-Sleman. This research is a qualitative descriptive study which is done by describing the teacher of English subject class 3 in SDS Prambanan, Sleman. Data collection techniques are done by interview. The results showed that in managing the classroom, there were several steps implemented by the subject teacher. First, the process of greeting, through greetings, recitations or stories at the beginning of the lesson. Second, seating arrangements so that teachers are able to mobilize or condition students in the classroom. Third, stage 3) Starting, by drawing the focus of students in advance on the teacher first before going to the book or worksheet. Fourth, get on with it (teacher activity provides material) and get on with them (teacher and student interaction) in the form of using several methods in learning. Fifth, get them out (the activity at the end of learning) by conveying the conclusions of the day and giving direction to students of the next material.Keywords: Class management, teacher, English lesson